Development of empirical relationship between the observed and the estimated ground acceleration values of small to moderate earthquakes in northwest (Gujarat) and northeast (NE) regions of India. Issue 1 (31st December 2022) - Choudhury, Pallabee; Roy, Ketan Singha; Kamra, Charu; Chopra, Sumer
Abstract: We developed empirical relationships between the ground accelerations directly obtained from the strong motion acceleration (SMA) data and the accelerations obtained by differentiating the velocity data from the broadband seismic records of the co-located sites, in the northwest (Gujarat) and northeast (NE) regions of India. In Gujarat, there are 215 earthquakes in the magnitude range of Mw 2.3–5.3, that occurred during 2006–2020, recorded by 18 co-located broadband seismograph and strong motion accelerograph stations. 94 events of magnitude range Mw 4.0–6.9, occurred during 2012–2017 are utilized from the 18 sites in the NE India. Using the developed relationships, we prepared ground motion distribution maps of few earthquakes that occurred in Gujarat and NE India. This is the first study of its kind for either or both the regions of India that assume great importance as priority areas of earthquake studies. The outcome of this study will help in predicting ground motion in the regions where SMA data is not available. Moreover, using the developed regression equation, a ground-shaking map can be generated instantly after an earthquake that will be of immediate use to the scientists, emergency response agencies, media, and general public.